Methods, forms and facilities of professional preparation of teachers-tutors in the conditions of the controlled from distance form of teaching - Osadchiy V.V (Kharkov National Pedagogical University, 2010)
The problems of professional preparation of teachers-tutors are studied. The features of application of methods are considered, forms and facilities of professional preparation of teachers-tutors in the conditions of the controlled from distance form of teaching. As expedient methods are selected: method of lecture, video trainings, interactive methods (role-playing, case studies, brainstorming), methods of reflection, control methods, exercises, laboratory method. By the forms of organization are electronic seminars, web-seminars, videos-seminars. By teaching facilities are electronic educational resources and services of network the Internet.